Species Diversity Regulates Ecological Strategy Spectra of Forest Vegetation Across Different Climatic Zones - Han, Xin; Xu, Yue; Huang, Jihong; Zang, Runguo (Frontiers in Plant Science, 2022)
Ecological strategy is the tactics employed by species in adapting to abiotic and biotic conditions. The ecological strategy spectrum is defined as the relative proportion of species in different ecological strategy types within a community. Determinants of ecological strategy spectrum of plant community explored by most previous studies are about abiotic factors. Yet, the roles of biotic factors in driving variations of ecological strategy spectra of forest communities across different geographic regions remains unknown. In this study, we established 200 0.04-ha forest dynamics plots (FDPs) and measured three-leaf functional traits of tree and shrub species in four forest vegetation types across four climatic zones. Based on Grime’s competitor, stress-tolerator, ruderal (CSR) triangular framework, and the StrateFy method, we categorized species into four ecological strategy groups (i.e., C-, S-, Int-, and R-groups) and related the ecological spectra of the forests to three species diversity indices [i.e., species richness, Shannon-Wiener index, and stem density (stem abundance)]. Linear regression, redundancy analysis, and variance partition analysis were utilized for assessing the roles of species diversity in regulating ecological strategy spectra of forest communities across different climatic zones. We found that the proportion of species in the C- and Int-groups increased, while the proportion of species in the S-group decreased, with the increase of three indices of species diversity. Among the three species diversity indices, stem abundance played the most important role in driving variations in ecological strategy spectra of forests across different climatic zones. Our finding highlights the necessity of accounting for biotic factors, especially stem abundance, in modeling or predicting the geographical distributions of plant species with varied ecological adaptation strategies to future environmental changes.